1977
DOI: 10.1055/s-0028-1098504
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of the Site of Upper Gastrointestinal Haemorrhage in Patients with Established Portal Hypertension

Abstract: Seventy-five endoscopies were performed in 60 patients known to have oesophageal varices presenting with further upper gastrointestinal haemorrhage during the previous 72 hours. A site of active bleeding was found at 50 of 75 examinations (67 percent) including all 21 patients endoscoped within three hours of the last haemorrhage. Variceal bleeding alone was seen in 40 of these 50 examinations (80%) and both varices and mucosal lesions were bleeding in 4 patients; mucosal lesions were an uncommon cause of haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Some studies reported cases of mucormycosis in patients with liver cirrhosis [ 11 – 13 ]. Upper gastrointestinal haemorrhage is the most common complication of liver cirrhosis, often seen in intensive units (ICU), which is usually caused by portal hypertension, and affecting clinical [ 14 16 ]. However, UGIB also is induced by a gastric ulcer as a complication of liver [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported cases of mucormycosis in patients with liver cirrhosis [ 11 – 13 ]. Upper gastrointestinal haemorrhage is the most common complication of liver cirrhosis, often seen in intensive units (ICU), which is usually caused by portal hypertension, and affecting clinical [ 14 16 ]. However, UGIB also is induced by a gastric ulcer as a complication of liver [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%